Iron- Refractory Iron Deficiency Anemia: Review Article - Eman Ahmed Abd -Elmawgood; Mohammed H. Hassan; Dina Hussein Mobark; Nagwan Ibrahim Rashwan (SVU - International Journal of Medical Sciences, 2024)
Background: IRIDA is an inherited recessive anaemia caused by a defect in the TMPRSS6 gene, which codes for the enzyme matriptase-2. This transmembrane serine protease suppresses hepcidin production, an iron regulator (suppressing intestinal absorption of iron). The biochemical results include normal to elevated hepcidin levels, inadequate transferrin saturation, and microcytic hypochromic anaemia. Although it can be identified at a later time, anaemia often manifests after birth. Despite the fact that effectiveness of oral iron therapy can depend on the degree of TMPRSS6 gene mutation. There are other therapies that either partially or totally correct anaemia such as intravenous iron infusions ,liposomal oral iron therapy ,anti hepcidin antibody and other information discussed later in these article . Objectives: to examine IRIDA's genesis, diagnosis, and therapy. Conclusion: When diagnosing microcytic anaemia, it is important to consider the separate disease entity known as iron refractory iron deficiency anaemia.